The Effect Of Circuit Training on The Improvement of Leg Muscle Explosiveness in Trained Badminton Players of Badminton UKM At Unesa - Fredian Yanuar Putra Febriyanto; Rohman, Fatkur; Wismanadi, Himawan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
This research is being overturned by a performance gap over the last year that has been demonstrated by the way he plays athletes. The circuit training training model is essential in a pile game to increase the explosive strength of the muscles of the membrane. The study aims to determine whether circuit training has an effect on the improvement of the explosive power of the muscles of the limbs on the UKM.Unesa bowling athletes. This research uses a type of experimental quasy research with pre-experimental methods and uses research design two groups pretest and posttest design. As for the sample in this study, there were 20 athletes. The data analysis technique used is a paired sample t-test.The results of the study showed that the influence of training circuit training on the increase in muscle membrane with significance values of 0.027 to 0.027 < 0.05, then H0 is rejected and H1 is accepted. So from the results of the t test indicated there was a significant difference between the addition of the circuit training of the experimental group and the control group. In conclusion, then with the addition of circuit training can have an impact in increasing the explosive power of the muscles of the limbs for the trained bulutangkis players of the State University of Surabaya.